The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1136/gut.30.12.1737
|View full text |Cite
|
Sign up to set email alerts
|

Defecography in normal volunteers: results and implications.

Abstract: SUMMARY Forty seven healthy young volunteers underwent defecographic examination to determine the range of normal findings. Normality was shown to encompass radiological features often considered pathological. These features included broad ranges of anorectal angle and pelvic floor descent which overlap with reported pathological states. Furthermore, the formation of rectocoeles during defecation was a very common finding in women. Finally, a subgroup of the volunteers had marginal anorectal function. The marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
398
4
28

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 703 publications
(441 citation statements)
references
References 17 publications
10
398
4
28
Order By: Relevance
“…Intussusception has been demonstrated in healthy volunteers and some degree of this disorder might be a normal finding. 23 We found that descending perineum syndrome was more frequently observed in males, contrary to previous studies. 24,25 Although we lack an explanation, we hypothesize that it could be due to the fewer numbers of men in our study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Intussusception has been demonstrated in healthy volunteers and some degree of this disorder might be a normal finding. 23 We found that descending perineum syndrome was more frequently observed in males, contrary to previous studies. 24,25 Although we lack an explanation, we hypothesize that it could be due to the fewer numbers of men in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…This is in agreement with previous studies. 23,26 The following risk factors were most commonly seen in women: Abnormal descend of the fetal head, the performance of instrumental deliveries, obesity, and chronic obstructive pulmonary disease. 27 Arnold et al published a case-series in which constipation did not disappear in most patients after rectocele repair.…”
Section: Discussionmentioning
confidence: 99%
“…Others have failed to demonstrate any correlation between defecography findings and surgical outcome (14,16) . Nevertheless, rectocele is rather frequently observed in asymptomatic nulliparous volunteers (34) . In this study the constipation score improved without surgical repair in approximately half the patients (clinical management alone = 33%; clinical management + biofeedback = 13.6%).…”
Section: Discussionmentioning
confidence: 99%
“…(27) Goei et al, 1989 (28) Shorvon et al, 1989 (29) Freimanis et al, 1991 (19) Mezwa et al, 1993 (18) Somers, 1994 (9) Ikenberry et al, 1996 …”
Section: Conclusãomentioning
confidence: 99%